تطبيق تقنيات الذكاء الاصطناعي في مكافحة الاتجار بالبشر: Application of artificial intelligence techniques in combating human trafficking - Alshamsi, Sultan Ghanem; Hasnizam bin Hashim,; Adzidah binti Yaakob, (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص الإنسان هو أيقونة الحياة وهو محور اهتمام العالم والجهات الأمنية التي توفر من أجله الميزانيات العامة لتحيق الرفاهية والتنمية الشاملة له، حيث تسعى المنظمات العالمية والوطنية والدساتير كافة إلى الحفاظ على الإنسان وحقه في الحياة أمناً مستقراً، فلا صلاح للأرض بدون الحفاظ على الإنسان وكرامته واحترام شخصيته، إذ كان لزاماً حماية الأشخاص من تلك الجرائم البشعة التي تتمثل في اختطاف الضعفاء منهم والمتاجرة بهم، إذ تبرز الإشكالية الرئيسية للبحث في الحفاظ على هؤلاء الأبرياء من براثن الشر التي تختفي خلف شاشات الحاسوب، ومن هنا يحاول الباحث الوصل الى مدى فاعلية تطبيقات الذكاء الاصطناعي في مكافحة تلك الجريمة، حيث تم اتباع المنهج الوصفي من خلال استعراض بيان مفهوم الاتجار بالبشر، كما تم استخدام المنهج التحليلي في البحث واستكشاف الطرق التي يتم بها إغراء واختطاف الأشخاص بها عبر قنوات التكنولوجية والمتاجرة بهم، كما تم التطرق إلى استخدام المنهج الاستقرائي من خلال البحث ومراجعة أدبيات البحث والمصادر والمراجع التي عالجت نفس موضوع البحث. وقد خرج البحث بعدد من النتائج أهمها هي أن ظاهرة الاتجار بالبشر هي ظاهرة موجودة، وتعاني منها كل شعوب العالم وليس دولة الإمارات بمفردها وبحسب التعامل معهـا؛ وأن تقنيات الذكاء الاصطناعي وتكنولوجيا المعلومات يمكـن أن تكـون جـزءاً مـن المشكلة حيث أن المجموعات الإجرامية المنظمة تتطور اساليبها و يمكن أن تستخدم تقنيات الذكاء الاصطناعي وتكنولوجيا المعلومات لتوسع كيانها وتسهل نشاطاتها الإجرامية في مجـالي الاتصالات والصفقات المالية ولتجنيد الضحايا واستغلالهم، وبناء على ذلك يوصي الباحثون المبادرة بالاستفادة من استعمال سائر أشكال تقنيات وتطبيقات الذكاء الاصطناعي في مجال تكنولوجيا المعلومات والاتصالات لإنشـاء قواعد بيانات معلوماتية بمتابعة ودراسـة وتحليل المستجدات التي لها علاقة بمشكلة الاتجار بالبشر وتبادلها مع الجهات المعنية. Abstract Man is the icon of life and he is the focus of the world’s attention and the security authorities that provide public budgets for him to achieve well-being and comprehensive development for him, as all international and national organizations seek to preserve man and his right to life in a stable security. It was necessary to protect people from these heinous crimes, which is represented in the kidnapping and trafficking of the weak, as the main problem of research is to preserve these innocent people from the clutches of evil that hide behind computer screens, and the researcher is trying to help the security official in searching for the effectiveness of artificial intelligence applications in Combating that crime, the descriptive approach was followed by reviewing the concept of human trafficking, and the analytical approach was used in the research and exploration of the ways in which people are lured and kidnapped through technological channels and traded with them, and the use of the inductive approach was also addressed through the research and review of the research literature And sources and references that dealt with the same research topic. The research came out with a number of results, the most important of which is that the phenomenon of human trafficking is an existing phenomenon, and all peoples of the world suffer from it, not the UAE alone and according to how it is dealt with. And that artificial intelligence techniques and information technology can be part of the problem, as organized criminal groups can use artificial intelligence techniques and information technology to expand and facilitate their criminal activities in the areas of communications and financial deals and to recruit and exploit victims. Accordingly, the researchers recommend that the initiative take advantage of the use of other forms of Techniques and applications of artificial intelligence in the field of information and communication technology to create information databases by following up, studying and analyzing developments related to the problem of human trafficking and exchanging them with the concerned authorities.